ANALISIS SWOT UNTUK MENENTUKAN STRATEGI PEMASARAN JASA LAUNDRY PADA CV. BOS CLEAN LAUNDRY DI KARAWACI TANGERANG - Muhamad Akbar, (JOEL: Journal of Educational and Language Research, 2022)
Rapid technological developments and changes in human lifestyles make some people choose to use laundry or laundry services to ease their needs. Laundry service businesses need to design a good marketing strategy to face competition. This study aims to conduct a SWOT analysis and formulate a marketing strategy for laundry services at CV. Boss Clean Laundry. This study uses a descriptive method with a qualitative approach, data collection techniques using interviews (oral and written) and observation. The data analysis technique uses a SWOT analysis through a SWOT matrix and a SWOT quadrant. The results of this study indicate that the company's strength factors in service quality, distribution, additional services, affordable prices, and available wet and dry areas. On the weak side, there is a lack of human resources, lack of time efficiency, a minimal production process, inappropriate distribution, and a lack of technological skills. On the opportunity factor is the number of rented and student boarding houses, customer satisfaction, and changes in people's lifestyles. On the threat side there is customer loyalty, a high level of business competition, price and quality competition and technology